Effect of a mobile phone-based intervention on post-abortion contraception: a randomized controlled trial in Cambodia - Chris Smith; Thoai D Ngo; Judy Gold; Phil Edwards; Uk Vannak; Ly Sokhey; Kazuyo Machiyama; Emma Slaymaker; Ruby Warnock; Ona McCarthy; Caroline Free (The World Health Organization, 2015)
Abstract Objective To assess the effect of a mobile phone-based intervention (mHealth) on post-abortion contraception use by women in Cambodia. Methods The Mobile Technology for Improved Family Planning (MOTIF) study involved women who sought safe abortion services at four Marie Stopes International clinics in Cambodia. We randomly allocated 249 women to a mobile phone-based intervention, which comprised six automated, interactive voice messages with counsellor phone support, as required, whereas 251 women were allocated to a control group receiving standard care. The primary outcome was the self-reported use of an effective contraceptive method, 4 and 12 months after an abortion. Findings Data on effective contraceptive use were available for 431 (86%) participants at 4 months and 328 (66%) at 12 months. Significantly more women in the intervention than the control group reported effective contraception use at 4 months (64% versus 46%, respectively; relative risk, RR: 1.39; 95% confidence interval, CI: 1.17-1.66) but not at 12 months (50% versus 43%, respectively; RR: 1.16; 95% CI: 0.92-1.47). However, significantly more women in the intervention group reported using a long-acting contraceptive method at both follow-up times. There was no significant difference between the groups in repeat pregnancies or abortions at 4 or 12 months. Conclusion Adding a mobile phone-based intervention to abortion care services in Cambodia had a short-term effect on the overall use of any effective contraception, while the use of long-acting contraceptive methods lasted throughout the study period.